The Effect of Self Management Education and Support in Improving The Self-Efficacy of Patients with Type 2 Diabetes Mellitus - Murtaqib Murtaqib; Rondhianto Rondhianto; Nailul Aizza Rizqiyyah (Universitas Padjadjaran, 2019)
Diabetes mellitus type 2 is a chronic disease that requires self-management. Self-efficacy of patients with type 2diabetes focuses on improving management education and support services. This study aimed to determine theeffect of diabetes self-management education and support on self-efficacy in patients with type 2 diabetes mellitusin Dr. Soebandi hospital Jember. This type of research was a quasi-experiment using a two-group pre-post-testdesign. The research sample consisted of 30 respondents from 15 controls and 15 consecutive sampling groups.Technique sampling used. Inclusion criteria included 1) diagnosed with type 2 diabetes mellitus; the level ofconsciousness is compos mentis; 2) aged 30–65 years. The statistical test used t-tests dependent and independentt-test. Stages there were 6 sessions. Implementation of 1-4 sessions in the hospital and at home 5–6 sessions patients.The results showed that a score of self-efficacy increased by 17:53 in the treatment group and 4.93 in the controlgroup (p=0.001). The results showed that there was a significant difference between self-efficacy, the treatmentgroup and the control group after administration amounted to 10.495 (p=0.001). The conclusion suggests that thereis a significant influence on the self-efficacy of patients with type 2 diabetes in Dr. Soebandi hospital Jember. It isexpected that this study found is a recommended intervention for health workers to improve the self-efficacy ofpatients with type 2 diabetes so as to improve healthy lifestyles, reduce complications, and improve quality of life.